A Juridical Analysis of Compensation Rights for Patient Victims of Medical Malpractice - G.Hidayat; H.Nugraha (The Medical Journal of Hospital Management and Health Law, 2025)
Introduction: Medical malpractice represents a critical intersection between healthcare delivery and legal accountability, where errors often result in severe patient injury or death. This study addresses the legal ambiguities surrounding the fulfillment of compensation rights for patient victims under Indonesian medical and civil law. Methods: Utilizing a normative juridical research method, this study analyzes primary, secondary, and tertiary legal materials, including statutory legislation, judicial precedents, and legal doctrines. Results: The findings reveal that while the Indonesian Civil Code, Health Law, and Medical Practice Law theoretically guarantee patient rights, the actual mechanism for securing compensation remains complex, costly, and heavily burdened by the onus of proof placed on the patient. Discussion: The discussion highlights a significant gap between statutory intent and judicial enforcement, emphasizing the need for a shift toward a strict liability or no-fault compensation system in medical disputes. Literature reviews further demonstrate that existing dispute resolution mechanisms, such as mediation, often fail due to unequal bargaining power between patients and medical institutions. Conclusions: This study concludes that comprehensive legal reforms are essential to streamline the compensation process, ensuring equitable protection for victims.